Fluoroquinolone resistance in Achromobacter spp.: substitutions in QRDRs of GyrA, GyrB, ParC and ParE and implication of the RND efflux system AxyEF-OprN. (6th November 2020) - Magallon, Arnaud; Roussel, Mathilde; Neuwirth, Catherine; Tetu, Jennifer; Cheiakh, Anne-Charlotte; Boulet, Baptiste; Varin, Véronique; Urbain, Victor; Bador, Julien; Amoureux, Lucie
Abstract: Background: Achromobacter are emerging pathogens in cystic fibrosis patients. Mechanisms of resistance to fluoroquinolones are unknown in clinical isolates. Among non-fermenting Gram-negative bacilli, fluoroquinolone resistance is mostly due to amino acid substitutions in localized regions of the targets (GyrA, GyrB, ParC and ParE) named QRDRs, but also to efflux. Objectives: To explore quinolone resistance mechanisms in Achromobacter. Methods: The putative QRDRs of GyrA, GyrB, ParC and ParE were sequenced in 62 clinical isolates, and in vitro one-step mutants obtained after exposure to fluoroquinolones. An in vitro mutant and its parental isolate were investigated by RNASeq and WGS. RT–qPCR and gene inactivation were used to explore the role of efflux systems overexpression. Results: We detected seven substitutions in QRDRs (Q83L/S84P/D87N/D87G for GyrA, Q480P for GyrB, T395A/K525Q for ParE), all in nine of the 27 clinical isolates with ciprofloxacin MIC ≥16 mg/L, whereas none among the in vitro mutants. The RND efflux system AxyEF-OprN was overproduced (about 150-fold) in the in vitro mutant NCF-39-Bl6 versus its parental strain NCF-39 (ciprofloxacin MICs 64 and 1.5 mg/L, respectively). A substitution in AxyT (putative regulator of AxyEF-OprN) was detected in NCF-39-Bl6. Ciprofloxacin MIC in NCF-39-Bl6 dropped from 64 to 1.5 mg/L following gene inactivation of either axyT or axyF . Substitutions in AxyT associated with overexpression of AxyEF-OprN were also detected in seven clinical strains with ciprofloxacin MIC ≥16 mg/L. Conclusions: Target alteration is not the primary mechanism involved in fluoroquinolone resistance in Achromobacter . The role of AxyEF-OprN overproduction was demonstrated in one in vitro mutant.